2004
DOI: 10.1002/dvdy.10502
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of the chicken Lmbr1 coding sequence and characterization of its role during chick limb development

Abstract: In the developing amniote limb, anteroposterior (A/P) patterning is controlled through secretion of the Sonic Hedgehog (SHH) protein by cells in the zone of polarizing activity (ZPA) located in the posterior mesoderm. In the chicken mutant oligozeugodactyly (ozd), Shh is expressed normally in the entire embryo with the exception that it is undetectable in the developing limbs; this results in the loss of specific bones in wings and legs. The ozd phenotype is similar to that of humans affected with acheiropodia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
1
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 26 publications
0
32
1
1
Order By: Relevance
“…Sequencing the coding and intronic regions of a single candidate gene, LMBR1, revealed base substitutions in the intronic MCS region located upstream of ZRS, termed preZRS, or pZRS, which exhibited a limb-specific enhancer activity and altered the expression pattern in the limb bud in a transgenic mouse when mutated. The mutational effect of pZRS was distinct from that of a ZRS reported previously (Maas and Fallon 2004).…”
Section: Ongenital Malformations Of the Vertebrate Limbcontrasting
confidence: 57%
See 1 more Smart Citation
“…Sequencing the coding and intronic regions of a single candidate gene, LMBR1, revealed base substitutions in the intronic MCS region located upstream of ZRS, termed preZRS, or pZRS, which exhibited a limb-specific enhancer activity and altered the expression pattern in the limb bud in a transgenic mouse when mutated. The mutational effect of pZRS was distinct from that of a ZRS reported previously (Maas and Fallon 2004).…”
Section: Ongenital Malformations Of the Vertebrate Limbcontrasting
confidence: 57%
“…The LMBR1 gene with 17 exons encodes a putative transmembrane protein homologous to a lipocalin receptor (Wojnar et al 2003). The expression of LMBR1 was not localized in developing mouse limbs , and its overexpression in a developing chick limb did not interfere with normal skeletal development (Maas and Fallon 2004). The targeted deletion of the first exon in a mouse resulted in a loss of distal limb structure (Clark et al 2001), while a deletion in exon 4 in a human caused a distal limb truncation called acheiropodia (Ianakiev et al 2001).…”
Section: Ongenital Malformations Of the Vertebrate Limbmentioning
confidence: 99%
“…S1, which is available online), and a related upstream sequence that is associated with polydactyly in dogs has been termed the ''pZRS'' (Park et al, 2008). Meanwhile, the chicken OZD mutant, which lacks Shh expression in the limbs and has a loss of digits, is associated with intron3 of the LMBR1 gene (Ros et al, 2003;Maas and Fallon, 2004) as is human Acheiropodia in which a deletion between intron 3 and 4 of LMBR1 causes a loss of limb structures distal to the elbows and knees . Genetic evidence from mouse has shown that the ZRS sequence acts in cis with Shh (Lettice et al, 2002), physically interacting with the Shh sequence specifically in limb bud tissue to regulate Shh expression (Amano et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…En ratones, la mutación provoca anomalías de reducción de miembros, mientras que, en pollos, si bien hay un patrón de expresión de este gen en el miembro en desarrollo, la modificación de su expresión no se vio asociada con la aparición de anomalías de miembros. 8 La expresividad clínica de la aqueiropodia ha mostrado escasa variabilidad. En los miembros superiores, la amputación, generalmente, ocurre a nivel del tercio inferior del húmero, aunque es frecuente observar, en el segmento terminal, una formación que remeda al cóndilo y, a veces, se encuentra articulada con un cúbito vestigial.…”
Section: Caso Clínicounclassified